An analysis of colleganza contracts in the Republic of Venice and its relationship to the Serrata of the Great Council - Merelo-Guervós, Juan J.; Molinari, M. Cristina (Social Network Analysis and Mining, 2025)
From its inception, the Republic of Venice was a state focused on maritime trade, an activity that required large amounts of capital and involved many risks. To meet these needs, the Republic used a type of contract called colleganza , a form of profit-sharing partnership by which a sedentary investor ( stans ) financed a travelling merchant ( tractor ). The colleganza benefited a large portion of the population and constituted a commercial as well as a social network. In this paper, we use an existing database of colleganza contracts to investigate access to the nobility in the Republic of Venice during the Serrata (1297–1323), a constitutional process through which membership in the Great Council, the most important political assembly of the republic, became hereditary and limited to noble families, making the patriciate the ruling class of Venice. We first show that there was no social stratification between the role of stans and tractor and that many families switched from one role to the other. Next, we investigate the probability of being admitted to the Great Council and find that it was higher for families who were more active in the colleganza , both in terms of the number of contracts and roles held, and who had higher DNSL-betweenness in the colleganza social network. We conclude that a strong presence in various roles in the colleganza contracts and centrality in the network were sources of social capital that could be harnessed to ensure the family’s social advancement and access to nobility.